Self and Culture in Nigerian Migrant and Travel Ethno-Autobiographical Poetry in English (2014)
Ethno-autobiographical poetry is a culturally constituted autobiographical poetry. Due to its subjectivity, it is regarded by critics as an unreliable construction of social history. Consequently, previous researches consider ethno-autobiographical poetry as essentially self-aggrandising, neglecting its form as a unique blend of both self and culture. Therefore, this study explored the cultural constitution of selected Nigerian migrant and travel literary ethno-autobiographical poetry, in terms of racism, ethos, and space, with a view to establishing its features as a source of social history. The diachronic perspective of the Genre Theory, which emphasises the historical and dynamic function and features of a genre, is adopted to conceptualise autobiography as ethno-autobiography. The historico-biographical method was used to explore how self and culture are constructed in four collections of purposively selected Nigerian migrant autobiographical poems: Tanure Ojaide‘s When it No Longer Matters Where You Live (No Longer Matters), Femi Oyebode‘s Master of the Leopard Hunt (Master), Olu Oguibe‘s Songs of Exile, Uche Nduka‘s The Bremen Poems, and two collections of poetic travelogues: Odia Ofeimun‘s London Letter and Other Poems (London Letter) and Remi Raji‘s Shuttlesongs: America (Shuttlesongs). The texts were subjected to critical textual analysis. Nigerian migrant and travel ethno-autobiographical poetry depicts an interplay of racism, ethos, and space in the authors‘ self construction. In Master, racism is portrayed in the persona‘s treatment as a racial ‗Other‘; ethos is depicted in the appropriation of Benin mythical art and ancestral beliefs as identity schema and for interrogating the episteme of Euro-American geo-space. Songs of Exile depicts racism in the persona‘s hybridity and identity crisis, but ethos in the conflict between his African imagination and Americans‘ individualistic lifestyle, which results from his encounter with the geo-cultural space of exile as a post-colonial subject. The Bremen Poems relates the persona‘s loneliness and vulnerability as a racial outsider, whereas ethos is depicted in his conflicting feelings of nostalgia for the homeland and love for the exilic space of Bremen as a city of refuge. In No Longer Matters, exile is associated with racial discrimination, individualism and deceptive glamour while the homeland is portrayed as oppressive and squalid resulting in the persona‘s conclusion that neither geo-space is conducive for self realisation. In London Letter, Lagos and London are depicted as racially and socially stratified and filthy; ethos is portrayed in the persona‘s queries of Nigerian emigrants‘ Eurocentric disposition and their flamboyant lifestyles as citizens and immigrants within the geo-cultural spaces of Lagos and London respectively. In Shuttlesongs, racism is portrayed in the historic slave trade and racial discrimination occluded by modern America‘s glamour while ethos is depicted in America‘s liberal democracy, human rights, and African American cultural values; the persona encountered these during visits to America‘s historic sites and geo-cultural spaces. The cultural constitution of selected Nigerian migrant and travel literary ethnoautobiographical poetry, in terms of racism, ethos, and space, is composed, respectively, of alterity, identity construction and epistemological orientation, and trans-spatiality. These features demonstrate ethno-autobiography‘s form as an expression of self and culture within the context of social history